2018
DOI: 10.1080/09540121.2018.1478384
|View full text |Cite
|
Sign up to set email alerts
|

Integrated access to care and treatment (I ACT) support groups for adolescents living with HIV in public healthcare facilities in South Africa: feasibility and acceptability for scaling up

Abstract: Integrated Access to Care and Treatment (I ACT) for adolescents is an educational support group initiative conducted monthly by trained healthcare providers (counsellors/health promoters). It follows a defined educational curriculum of six topics including, HIV/AIDS, disclosure, sexual and reproductive and mental health. Qualitative assessments, conducted midway of I ACT implementation at four primary healthcare facilities in North West province, South Africa, aimed to explore the perceptions of healthcare pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…It also builds on a small but growing number of HIV program acceptability studies with adolescents and young adults in sub-Saharan Africa [29]. Similar to this research, we found that offering social support within a safe, stigma-free environment is highly acceptable to youth with HIV [14,30]. Such an environment allows youth to feel comfortable discussing personal challenges and developing trusting relationships, thus motivating them to accept their HIV status [29,31].…”
Section: Discussionsupporting
confidence: 71%
“…It also builds on a small but growing number of HIV program acceptability studies with adolescents and young adults in sub-Saharan Africa [29]. Similar to this research, we found that offering social support within a safe, stigma-free environment is highly acceptable to youth with HIV [14,30]. Such an environment allows youth to feel comfortable discussing personal challenges and developing trusting relationships, thus motivating them to accept their HIV status [29,31].…”
Section: Discussionsupporting
confidence: 71%
“…All 7 support group interventions provided psychosocial or educational support related to HIV, and 5 worked only with young adults living with HIV. One group intervention was delivered through both a social media platform and in-person meetings (53), one was a family based support intervention with adolescent-parent dyads (33), four were linked to public healthcare facilities (42, 47, 54, 55) and one was a community intervention (43).…”
Section: Resultsmentioning
confidence: 99%
“…Fear of the procedure, concerns with the cost and validity of the test, and inadequate emotional support were reasons given for lack of acceptability (64, 75, 76). Support group interventions were considered acceptable because of the emotional support provided and because young adults found the groups to be empowering and were able to discuss HIV-related issues in a stigma-free environment (42, 47, 53, 55).…”
Section: Resultsmentioning
confidence: 99%
“…Some, including Ybarra, 2014 [22], and Smith, 2016 [23], developed questionnaires using Likert scales to assess outcomes of acceptability and feasibility. Others, including Barker, 2019 [29] and James, 2018 [27], conducted interviews and focus groups with participants using semi-structured interview guides. Secondary data and process data noting things like consent, continued attendance, and referral requests for additional resources were also documented as implementation science outcomes, particularly acceptability [31,33,38].…”
Section: Implementation Science Characteristicsmentioning
confidence: 99%